Nilai Sosial dan Estetika dalam Novel 5 Cm Karya Donny Dhirgantoro - Abdul Wachid; Utami, Sri; Sugianto, Iwan (GERAM: Gerakan Aktif Menulis, 2023)
The novel "5 Cm" by Donny Dhirgantoro contains social and aesthetic values, which makes it a suitable subject for research aiming to describe these values. This study adopts a qualitative descriptive research approach, using data obtained from the novel "5 Cm" itself. The data collection method employed in this study involves reading the novel and taking detailed notes. The data analysis method utilizes descriptive techniques to examine the collected data. The researchers also conducted data validation to enhance the reliability of the study. The findings of this research reveal the presence of three social values in the novel "5 Cm": material values, vital values, and spiritual values as presented by Notonegoro. Additionally, the novel also encompasses aesthetic values, including asexual beauty, natural beauty, and alkaline beauty. This research holds significance for further studies and readers, as it allows them to explore the values conveyed in the novel and uncover the underlying meanings in "5 Cm."